2011
DOI: 10.1080/ac.66.3.2114132
|View full text |Cite
|
Sign up to set email alerts
|

Role of insulin receptors in myocardial ischaemia-reperfusion injury during cardiopulmonary bypass

Abstract: A decrease in insulin receptor expression is a cause of post-bypass insulin resistance, and this decrease is initiated at the mRNA level. Increased insulin resistance leads to excessive reliance on myocardial glycogen as an energy source and a deficit in energy substrates that contributes to cardiac dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Severe cardiac injury and cardiac dysfunction are the main consequences of CPB surgery . Consistent with these findings, our data showed that the levels of cardiac injury biomarkers, including plasma creatine kinase MB and troponin I, significantly elevated 2 hours after CPB (Figure A,B).…”
Section: Resultssupporting
confidence: 87%
“…Severe cardiac injury and cardiac dysfunction are the main consequences of CPB surgery . Consistent with these findings, our data showed that the levels of cardiac injury biomarkers, including plasma creatine kinase MB and troponin I, significantly elevated 2 hours after CPB (Figure A,B).…”
Section: Resultssupporting
confidence: 87%
“…The lungs are one of the most vulnerable solid organs. There are several clinical conditions wherein IR-induced ALI is implicated [ 45 47 ]. Numerous attempts have been made to preserve lung viability after lung transplantation, pulmonary thrombo-embolectomy, or cardio-pulmonary by-pass [ 45 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, beta cells secretory granules was affected under condition of poor perfusion, oxidative stress, or infections, which might change the process of converting pro-insulin to insulin and C-peptide and further result in pancreatic beta cells dysfunction. 14 , 15 …”
Section: Discussionmentioning
confidence: 99%